69: Bayley-III Outcomes at 18–21 Months Corrected Age for a Canadian Cohort of Infants Born <29 Weeks Gestation. Issue 6 (1st June 2014) - Creighton, D; Lodha, A; Majnemer, A; Moddemann, D; Church, P; Lee, D; Lefebvre, F
Abstract: BACKGROUND: The Canadian Neonatal Follow-up Network (CNFUN) monitors the outcomes of infants born <29 weeks gestational age (GA) at 26 neonatal follow-up centres across Canada. The use of a standardized assessment tool, the Bayley Scales of Infant and Toddler Development – Third Edition (Bayley-III), at a common age allows for systematic evaluation of cognitive, language and motor development across sites. OBJECTIVES: To describe the cognitive, language and motor development at 18 to 21 months corrected age (CA) for the cohort of CNFUN preterm infants born April 1 2009 to July 1 2011. DESIGN/METHODS: Trained and qualified Bayley-III testers administered the assessment of cognitive, language and motor abilities to preterm infants at 18 to 21 months CA. Bayley-III composite scores are normally distributed and have a mean of 100, SD 15. Scores <85 are considered below the normal range and are defined here as indicating impairment. Results are presented by gestational age at birth (GA) and by birthweight (BW) category. RESULTS: Of 2528 infants born <29 weeks GA, 2109 (83.4%) were seen in follow-up at 18 to 21 months CA. Cognitive composite scores were obtained for 1958 (92.8%) infants, language composite scores for 1899 (90.0%), and motor composite scores for 1887 (89.5%). The table shows outcomes by GA and by BW category. CONCLUSIONS: A high rate of below normal scores was evident for infants born at younger gestational ages and lower birthweights, indicating impairments at 18 to 21 months corrected age, especially with respect to language and motor development. Gestational age specific data on outcomes at 18 to 21 months will be helpful for counseling.